At the Forefront of the Mucosal Barrier: The Role of Macrophages in the Intestine - Barbara Ruder; Christoph Becker (Cells, 2020)
Macrophages are part of the innate immunity and are key players for the maintenance of intestinal homeostasis. They belong to the group of mononuclear phagocytes, which exert bactericidal functions and help to clear apoptotic cells. Moreover, they play essential roles for the maintenance of epithelial integrity and tissue remodeling during wound healing processes and might be implicated in intestinal tumor development. Macrophages are antigen-presenting cells and secrete immune-modulatory factors, like chemokines and cytokines, which are necessary to activate other intestinal immune cells and therefore to shape immune responses in the gut. However, overwhelming activation or increased secretion of pro-inflammatory cytokines might also contribute to the pathogenesis of inflammatory bowel disease. Presently, intestinal macrophages are in the center of intense studies, which might help to develop new therapeutic strategies to counteract the development or treat already existing inflammatory diseases in the gut. In this review, we focus on the origin of intestinal macrophages and, based on current knowledge, discuss their role in the gut during homeostasis and inflammation, as well as during intestinal wound healing and tumor development.